2008
DOI: 10.1056/nejmoa072727
|View full text |Cite
|
Sign up to set email alerts
|

Severe Anemia in Malawian Children

Abstract: There are multiple causes of severe anemia in Malawian preschool children, but folate and iron deficiencies are not prominent among them. Even in the presence of malaria parasites, additional or alternative causes of severe anemia should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
394
10
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 389 publications
(435 citation statements)
references
References 79 publications
26
394
10
5
Order By: Relevance
“…Even in children with severe anaemia (haemoglobin concentration <50 g/l), there is no evidence of folate deficiency, and severe anaemia is not associated with plasma folate concentrations (Calis et al , 2008). …”
Section: Evidence Of Folate Deficiencymentioning
confidence: 99%
“…Even in children with severe anaemia (haemoglobin concentration <50 g/l), there is no evidence of folate deficiency, and severe anaemia is not associated with plasma folate concentrations (Calis et al , 2008). …”
Section: Evidence Of Folate Deficiencymentioning
confidence: 99%
“…4 This raises the possibility of development of a POC device for non-invasive diagnosis of iron deficiency, which could be very useful in the blood donation setting. A POC test could also be of value in developing countries where high burdens of anemia are attributable to iron deficiency and infectious diseases such as malaria, 37 and where targeted therapy (iron supplementation or antimicrobials) for the anemia is advisable. 38 A potential limitation of this approach is the higher pre-analytical variability associated with urine (as compared with serum) hepcidin measurements.…”
Section: S-r Pasricha Et Almentioning
confidence: 99%
“…Epidemiological studies (Calis et al, 2008;George et al, 2012), and early nutrition-based animal models (Hodges et al, 1978) found a strong association of vitamin A deficiency with anaemia in humans. Indeed, anaemia associated with nutritional deficiencies including vitamin A deficiency is a serious health problem, especially in developing countries.…”
mentioning
confidence: 99%